Wychowanie do wspólnoty parafialnej jako zadanie szkolnej lekcji religii - Osial, Wojciech (Studia Pastoralne, 2008)
The article entitled „Formation Towards Parish Community as the Goal of Religious Education in Schools” is an attempt to describe the role and meaning of religious education in the process of making the parish into a community. The author proves that the religious education inschools can greatly influence to transform the parish into community and the meaning of catechetical instruction cannot be diminished. This analysis is based on the correlation between the catechetical teachingin schools and the pastoral-catechetical activity in the parish. Fr. W. Osial relates first how the catechetical task of formation towards the community is viewed in the documents of the Church. The documents say that this is one of the six fundamental goals of catechesis. The second part of the article is an analysis of the content and forms of education for the community. Numerous and specific examples of the catechetical activity inschools are presented here and are divided into short and long-term (based on the formation in various religious groups) activities. In the last part the author explores the question of the role of the teacher in the process of drawing the pupils into the parish. The teacher’s attitude is one of the most important factors in influencing the participation of young people in the initiatives directed to them. The teacher’s importance as a role model is also stressed, as well as his personal engagement and openness to the problems of youth.